Corporatisation and corporate governance in China's economic transition - Lin, C (University of Oxford, 2000)
China has sought to improve enterprise performance not through privatisation as in other transition economies, but through corporatisation as means of improving corporate governance. Actual governance practices of corporatised Chinese firms are however seriously defective, characterized by excessive power of CEO's, insider control and collusion, lack of safeguards for minority shareholders and weak transparency. These shortcomings are attributable to factors such as cultural and political traditions, uncompetitiveness of markets, poor legal enforcement, weak debt and equity markets, but above all to continued state dominance in ownership and control of the corporate sector and listed companies. Corporatisation, nevertheless, has created a regime conducive to implementing measures for improving corporate governance.